Feeding on an exotic host plant enhances plasma levels of phenoloxidase by modulating feeding efficiency in a specialist insect herbivore - Mo, Carmen; Smilanich, Angela M. (Frontiers in Physiology, 2023)
Background: Exotic plant species represent a novel resource for invertebrates and many herbivorous insects have incorporated exotic plants into their diet. Using a new host plant can have physiological repercussions for these herbivores that may be beneficial or detrimental. In this study, we compared how using an exotic versus native host plant affected the immune system response and feeding efficiency of a specialist lepidopteran, the common buckeye (Junonia coenia: Nymphalidae, Hübner 1822). Materials and Methods: In a lab experiment, larvae were reared on either the exotic host plant, Plantago lanceolata (Plantaginaceae), or the native host plant, Mimulus guttatus (Plantaginaceae). Beginning at second instar feeding efficiency data were collected every two days until fifth instar when immune assays were performed. Immune assays consisted of standing phenoloxidase activity, total phenoloxidase activity, and melanization. Results: Interestingly, we found that all three immune system parameters were higher on the exotic host plant compared to the native host plant. The exotic host plant also supported higher pupal weights, faster development time, greater consumption, and more efficient approximate digestibility. In contrast, the native host plant supported higher efficiency of conversion of ingested and digested food. The relationship between immunity and feeding efficiency was more complex but showed a large positive effect of greater host plant consumption on all immune parameters, particularly for the exotic host plant. While not as strong, the efficiency of conversion of digested food tended to show a negative effect on the three immune parameters. Conclusion: Overall, the exotic host plant proved to be beneficial for this specialist insect with regard to immunity and many of the feeding efficiency parameters and continued use of this host plant is predicted for populations already using it.